FAMILY CONFERENCING - Dirk J Louw; Arda Spijker (Obiter, 2022)
The notion of propagating children’s rights and developing the aspirations of youth has developed internationally since the 1960s (United Nations Declaration of the Rights of the Child 1959). Although it is difficult to give a precise definition of the term “children’s rights”, there is a general acceptance of the idea that children have rights, which can be concluded from the fact that 192 countries have ratified the United Nations Convention on the Rights of the Child (1989) (hereinafter “the Children’s Convention”, ratified by South Africa on 16 June 1995). Section 28 of the Constitution of the Republic of South Africa Act, 1996 gives effect to the acceptance of the idea that children have rights by providing a list of nine specific rights for children. In addition, children are also entitled to all other rights in the Bill of Rights that are applicable to them, with the exception of the right to vote in section 19(3), which explicitly refers to “every adult citizen” (Bekink and Brand “Constitutional Protection of Children” in Davel (ed) Introduction to Child Law in South Africa (2000) 178). Moreover, section 28(2) of the Constitution provides that “a child’s best interests are of paramount importance in every matter concerning the child”. Article 3(1) of the Children’s Convention and article 4(1) of the AfricanCharter on the Rights and Welfare of the Child (1990) (hereinafter “the African Charter”, ratified by South Africa on 7 January 2000), both recognise that the “best interests of a child” shall be “a” or “the” primary consideration in all actions concerning children. The Children’s Act 38 of 2005 (hereinafter “the Children’s Act”), which has not come into operation yet, also refers in sections 2(b)(iv) (Objects of Act), 6, 7 and 9 to the “best interests of the child standard”. Thus every decision which may impact on the child must be guided by the “child’s best interests”. The duty to secure this right lies with the legislature and the implementation lies mainly with the courts. However, the Children’s Act also provides for alternative mechanisms, thereby improving the right of children to participate in decisions affecting them. This paper focuses on one alternative, namely family conferencing. Some aspects of the Children’s Act and the Child Justice Bill will be discussed (par 2) and then the focus will shift to family conferencing: What is it about (par 3)? Will it suit the South African context (par 4)? How should it be applied (par 5)?